The Readiness of E-Publishing Among Malaysian Book Publishers - Katan, Rozilah; Mustafa, Siti Ezaleila; Adnan, Hamedi Mohd (Springer Verlag, 2018)
Advancements in digital technology are making waves in the publishing industry and e-publishing is starting to make its mark in the market. Although publishers view e-publishing as an opportunity to exploit products and new distribution channels, some of them are seeing this development as a risk rather than an opportunity, and thus are not willing to participate in these changes. This study was conducted to determine the readiness of e-publishing among Malaysian book publishers based on the E-Publishing Readiness Assessment Model. The results found that publishers in Malaysia are prepared in terms of infrastructure and human resources. However, only a small percentage of them are willing to practice e-publishing by publishing at least one e-book, while the majority is taking a wait and see approach before they start issuing e-books. Interviews with two companies displaying high levels of e-readiness and low e-readiness, showed a willingness depend on the decision of the company’s top management. In addition, external factors such as market demand, technological pressure, competition, consumer habits and police and government policies also affect the results of the top management to run e-publishing in their respective companies. Through these findings, the government and agencies involved in the publishing industry may be able to help find a solution when designing a strategy for improving e-publishing practices in Malaysia.